Recomposing Ecopoetics : North American Poetry of the Self-Conscious Anthropocene - Keller, Lynn, 1952- (Book collections on Project MUSE., 2017)
"This book grapples with key cultural and environmental conundrums that confront us now: the scale of planetary change, toxicity, plastics, apocalypticism, human relations to nonhuman animals, place in a globalized world, and environmental justice issues. Analyzing work by contemporary North American poets --from Evelyn Reilly and Juliana Spahr to Ed Roberson and Jena Osman--this study examines poetry of the "self-conscious Anthropocene," a period in which there is growing awareness of the scale and severity of human effects on the planet. This study brings cutting-edge work in ecocriticism to bear on a diverse archive of contemporary environmental poetry and offers the environmental humanities new ways to understand the cultural and affective dimensions of the Anthropocene"--